Active faults, deformation rates and Quaternary paleogeography at Kyparissiakos Gulf (SW Greece) deduced from onshore and offshore data - Papanikolaou, Dimitrios; Fountoulis, Ioannis; Metaxas, Christoforos (Quaternary International, 2007)
Kyparissiakos Gulf forms a 45 km long zone located at 70-80 km east from the Hellenic trench with a general direction NNW-SSE. Onshore studies show the existence of several neotectonic horsts and grabens bounded by E-W trending normal faults. Thrust sheets of the underlying Hellenides crop out within the horst areas and younger sediments, mostly Lower Pleistocene, have been deposited in the grabens. The age of the marine sediments is mostly Lower Pleistocene. Throw rate on the normal faults varies between 0.7 and >1.0 mm/yr, accommodating extension in the N-S direction. Subsidence rates during Early Pleistocene are between 0.1 and 0.3 mm/yr, whereas uplift rates during Middle Pleistocene-Present are between 0.18 and 0.50 mm/yr. Offshore data were obtained using bathymetric and air-gun litho-seismic profiles. The shelf has been disrupted by active faults with several meters of throw. Average Holocene throw rates are 0.4-0.6 mm/yr, but in some areas adjacent Filiatra and Olympia values greater than 3 mm/yr are detected. Holocene and Upper Pleistocene marine sediments thicken gradually to the north, as do the marine Lower Pleistocene sediments onshore. A NNW-SSE offshore longitudinal fault parallel to the Kyparissiakos coast with throw rate above 3 mm/yr is the dividing structure between the uplifted coastal area and the present-day gulf. This indicates a major change in paleogeography between Early and Middle Pleistocene. Present-day transition from E-W compression in the Hellenic Trench to E-W extension in the Kyparissiakos Gulf and to N-S extension in Western Peloponnesus is discussed. The development of E-W structures in Western Peloponnesus since Latest Pliocene may be related to the Central Hellenic Shear Zone, which accommodates differential GPS rates between Northern Greece and Southern Peloponnesus.